Photon Not Massless: A Possible New Theorem - Puccini, Antonio (European Journal of Applied Sciences, 2024)
As we all know, the photon(P), or light particle, is universally considered as a massless particle, in the sense that it is attributed a zero restmass, due to the fact that there is no P at rest, since its main characteristic is that it is always in motion, travelling at relativistic speeds. However, a fair portion of the scientific community admits that, being also a quantum of energy, when it is fired, the P can be considered as having a mass, which it would retain throughout its journey. It is like saying that the P has a non-zero relativistic mass, which can plausibly be considered as the dynamic mass of P which, in our opinion, would coincide with the momentum(p) of the P. It is the Bohr Complementarity Principle that would hide this mass when the P is in motion. For example, our calculations show that the p-value of an optic P is p =1.325∙10-22 [g× cm/s]. On the other hand, there are numerous mechanical effects induced by the possible mass carried by P. Indeed, the P produces a recoil effect in the atom that emits it, or deflects the path of the affected particle (scattering effect), as well as, by striking an atom, it can detach electrons from it (photo-electric effect), or it can even transform itself, alone or by colliding with another P, into a real and tangible mass. As is well known, this is the materialisation of energy whereby, from the collision between two photons (considered massless), an electron-positron pair is generated, as if from nothing, each having a restmass equal to 0.511 MeV!